The Outstanding Filipino (TOFIL) awardee for 1998 in the field of business - del Rosario, Ramon V., Sr. (Animo Repository, 1998)
La Salle alumnus Ramon V. del Rosario, Sr. (BSC '38) was chosen as The Outstanding Filipino (TOFIL) awardee for 1998 in the field of business. Del Rosario received his award on December 8, 1998, at the Cultural Center of the Philippines.